Affecting Factors on The Timing of The Issuance of The Report of The External Auditor of The Accounts of Iraqi Banks: An Empirical Study on The Iraqi Banks Listed in Iraqi Stock Exchange - Adnan Nader Hammed makhmury; Ismael Saleh khaland (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aims to study the effect of many factors (Audit office size, disclosure instructions according to the Iraqi Securities Commission, the size of audit fees) on the timing of the issuance of the report of the external auditor of the accounts of Iraqi banks. The sample consists of (19) Iraqi banks listed in the Iraqi market for securities for the period from 2012 to 2020, To achieve the objectives of the research, a model was developed using multiple regression, which included the factors above, such as independent variables and the timing of issuing external auditor reports as a dependent variable. The results showed that the regression model is highly significant in statistical terms and therefore reliable to, where the value of F was (80.412) with a significant level of 0.000, and therefore it can be relied upon to predict the values of the dependent variable. The results showed that Iraqi banks issue their external auditor reports at an average of (130.877) days from the end of the financial year. The results of the study showed the existence of a statistically significant significant relationship between the number of auditing offices and the time taken for the examination and audit process and the issuance of the external auditor's report for the accounts of Iraqi banks listed in the Iraq Stock Exchange. The results indicate the existence of a positive, moral relationship with statistical significance between the disclosure instructions of the Securities Commission and the time taken for the examination and auditing process and the issuance of the published external auditor's report for the Iraqi shareholding banks. This indicates that the external auditor adheres to the disclosure instructions issued by the Iraqi Securities Commission. The results indicate that there is no significant statistically significant relationship between the size of the auditing fees and the time taken for the examination and auditing process and the issuance of the external auditor's report for the accounts of Iraqi banks listed in the Iraq Stock Exchange.